Fluorine-containing polyarylether containing cross-linked network structure as well as preparation method and application of fluorine-containing polyarylether

By using fluoropolyarylether containing crosslinking network structure in electronic devices, combining low-polar trifluoroisopropyl and perfluorobiphenyl structures to form a crosslinking network, the high dielectric constant and mechanical in the prior art are solved. The problems of poor performance and insufficient thermal stability achieve low dielectric performance and excellent mechanical and thermal stability, and are suitable for electronic equipment.

CN119192557AInactive Publication Date: 2024-12-27SHANDONG XINGSHUN NEW MATERIAL JOINT CO LTD

Patent Information

Application Number
CN202411345175.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art is difficult to achieve materials with low dielectric constant, excellent mechanical properties, thermal stability and processing properties in electronic devices at the same time, resulting in problems such as resistance-capacitance delay, noise enhancement, and increased power loss.

Method used

Using fluoropolymer ethers containing crosslinking network structures, the dielectric constant is reduced by introducing low-polar trifluoroisopropyl and perfluorobiphenyl structures, and crosslinking is formed by reaction between amino side groups and epoxy groups. Network, limits segment movement, improves dimensional stability and thermal stability.

Benefits of technology

It achieves low dielectric properties, excellent mechanical properties and thermal stability, reduces dielectric constant, improves the free volume and segment stability of polymers, and is suitable for communications and microelectronics fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192557A_ABST
    Figure CN119192557A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of low dielectric materials, in particular to fluorine-containing polyarylether containing a cross-linked network structure as well as a preparation method and application of the fluorine-containing polyarylether. The preparation method comprises the following steps: by taking 2, 2-bis (3-amino-4-hydroxyphenyl) hexafluoropropane, 2, 2-bis (4-hydroxyphenyl) hexafluoropropane and perfluorobiphenyl as raw materials, firstly carrying out aromatic nucleophilic polycondensation reaction to obtain fluorine-containing polyarylether containing an amino structure, and further carrying out condensation polymerization on the fluorine-containing polyarylether and 1, 2-bis (3-amino-4-hydroxyphenyl) hexafluoropropane to obtain the fluorine-containing polyarylether containing the amino structure. And carrying out amino epoxy curing reaction on 1, 6-hexanediol diglycidyl ether to obtain the fluorine-containing polyarylether containing the cross-linked network structure. According to the fluorine-containing polyarylether containing the cross-linked network structure, the perfluorobiphenyl structure with low polarity, the trifluoroisopropyl group with large free volume and the cross-linked network structure are simultaneously and synergistically introduced, so that the dielectric constant of the material is effectively reduced; meanwhile, the rigid biphenyl structure improves the dimensional stability and thermal stability of the material, so that the fluorine-containing polyarylether has important potential application value in the field of microelectronics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of low dielectric materials, and in particular to a fluorine-containing polyarylether having a cross-linked network structure, and a preparation method and application thereof. Background Art

[0002] With the rapid development of electronic information technology, electronic devices are becoming increasingly functional and miniaturized. Integrated circuits, as the "nervous system" of electronic devices, are also becoming smaller in size. This increases resistance-capacitance (RC) delays, resulting in increased noise, increased power loss, signal delays, and other problems. Currently, copper with lower resistivity is used to replace aluminum in traditional processes as metal wires to effectively reduce the impact of resistance. In addition, the dielectric constant of the interlayer dielectric material must be reduced to reduce the capacitance effect and reduce the impact of capacitance on delay.

[0003] The traditional strategy is to introduce pore structures or hollow fillers into the material to achieve the purpose of reducing the dielectric constant, because the dielectric constant of air is 1. However, this method causes a large loss of mechanical properties of the material, increases water absorption, and the process is complicated, making it difficult to meet the requirements.

[0004] Organic polymers usually have low dielectric constants, excellent processing properties and mechanical properties, and are currently the focus of researchers. However, organic polymers also have disadvantages such as poor heat resistance and poor thermal stability, and cannot meet the processing temperature of the processing process. Therefore, it is key to study and prepare materials that have excellent dielectric properties, mechanical properties, thermal stability and processing properties. Summary of the invention

[0005] The object of the present invention is to provide a fluorinated polyarylether containing a cross-linked network structure and a preparation method and application thereof. The fluorinated polyarylether containing a cross-linked network structure has low dielectric properties and excellent mechanical properties, thermal stability and processing properties.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a fluorinated polyarylether having a cross-linked network structure, which has a structure shown in Formula 1:

[0008]

[0009] Among them, the value range of x is 0.1~0.4, and the value range of n is 60~90.

[0010] The present invention also provides a method for preparing the fluorinated polyarylether having a cross-linked network structure described in the above technical solution, comprising the following steps:

[0011] Carrying out an amino-epoxy curing reaction of a compound having a structure represented by Formula 2 and a compound having a structure represented by Formula 3 in an organic solvent to obtain the fluorinated polyarylether having a cross-linked network structure;

[0012]

[0013] Among them, the value range of x is 0.1~0.4, and the value range of n is 60~90.

[0014] Preferably, the molar ratio of the amino group in the compound having the structure shown in Formula 2 to the epoxy group in the compound having the structure shown in Formula 3 is 1:2.

[0015] Preferably, the method for preparing the compound having the structure of Formula 2 comprises the following steps:

[0016] 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane, 2,2-bis(4-hydroxyphenyl)hexafluoropropane, perfluorobiphenyl, potassium carbonate and N,N-dimethylacetamide are mixed and subjected to aromatic nucleophilic polycondensation reaction to obtain the compound having the structure of formula 2.

[0017] Preferably, the molar amount of the perfluorobiphenyl is equal to the sum of the molar amounts of the 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane and the 2,2-bis(4-hydroxyphenyl)hexafluoropropane;

[0018] The molar ratio of the 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane to the 2,2-bis(4-hydroxyphenyl)hexafluoropropane is (1-4):(9-6).

[0019] Preferably, the molar ratio of potassium carbonate to perfluorobiphenyl is (1-2):1;

[0020] The ratio of the mass of the N,N-dimethylacetamide to the total mass of the 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane, 2,2-bis(4-hydroxyphenyl)hexafluoropropane and perfluorobiphenyl is (4-6):1.

[0021] Preferably, the temperature of the aromatic nucleophilic polycondensation reaction is 80-90° C. and the time is 4-6 hours.

[0022] Preferably, the temperature of the amino-epoxy curing reaction is 100-140° C. and the time is 12-24 hours.

[0023] The present invention also provides the use of the fluorinated polyarylether containing a cross-linked network structure described in the above technical solution or the fluorinated polyarylether containing a cross-linked network structure prepared by the preparation method described in the above technical solution in the field of communications or microelectronics.

[0024] Preferably, the fluorinated polyarylether containing a cross-linked network structure is in the form of a fluorinated polyarylether membrane, and the preparation process of the fluorinated polyarylether membrane comprises the following steps:

[0025] Mixing a compound having a structure represented by Formula 2, a compound having a structure represented by Formula 3, and an organic solvent to obtain a mixed solution;

[0026] The mixed solution is formed into a film and solidified to obtain a fluorinated polyarylether film.

[0027] The present invention provides a fluorinated polyarylether having a structure shown in Formula 1:

[0028]

[0029] Among them, the value range of x is 0.1~0.4, and the value range of n is 60~90.

[0030] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0031] 1) The fluorinated polyarylether with a cross-linked network structure of the present invention reduces the polarizability and the dielectric constant by introducing a low-polarity trifluoroisopropyl group; at the same time, the large volume trifluoroisopropyl group also increases the free volume of the polymer, reduces the degree of polymer chain stacking, and further reduces the dielectric constant;

[0032] 2) The fluorine-containing polyarylether with a cross-linked network structure of the present invention increases the fluorine content by introducing a perfluorobiphenyl structure, and the low-polarity fluorine reduces the dielectric constant; the rigid benzene ring improves the dimensional stability and thermal stability;

[0033] 3) The fluorinated polyarylether containing a cross-linked network structure of the present invention forms a cross-linked network by introducing amino side groups to react with epoxy groups, thereby restricting the movement of chain segments and reducing the dielectric constant. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 is the PAE-1 described in Example 1 1 H-NMR spectrum;

[0035] Figure 2 is the PAE-2 described in Example 2 1 H-NMR spectrum;

[0036] Figure 3 is the PAE-3 described in Example 3 1 H-NMR spectrum;

[0037] Figure 4 is the PAE-4 described in Example 4 1 H-NMR spectrum;

[0038] Figure 5The fibrous fluorinated polyarylether containing amino structure described in Examples 1 to 4 is partially 1 H-NMR spectrum;

[0039] Figure 6 The infrared comparison spectra of Co-PAE-4 described in Comparative Example 4 and CL-Co-PAE-4 described in Example 4 are shown;

[0040] Figure 7 This is a graph showing the relationship between the dielectric constant and the change in electric field frequency for Co-PAE-1 described in Comparative Example 1, Co-PAE-2 described in Comparative Example 2, Co-PAE-3 described in Comparative Example 3, Co-PAE-4 described in Comparative Example 4, CL-Co-PAE-1 described in Example 1, CL-Co-PAE-2 described in Example 2, CL-Co-PAE-3 described in Example 3, and CL-Co-PAE-4 described in Example 4. DETAILED DESCRIPTION

[0041] The present invention provides a fluorinated polyarylether having a cross-linked network structure, which has a structure shown in Formula 1:

[0042]

[0043] Among them, the value range of x is 0.1~0.4, and the value range of n is 60~90.

[0044] The present invention also provides a method for preparing the fluorinated polyarylether having a cross-linked network structure described in the above technical solution, comprising the following steps:

[0045] Carrying out an amino-epoxy curing reaction of a compound having a structure represented by Formula 2 and a compound having a structure represented by Formula 3 in an organic solvent to obtain the fluorinated polyarylether having a cross-linked network structure;

[0046]

[0047] Among them, the value range of x is 0.1~0.4, and the value range of n is 60~90.

[0048] In the present invention, unless otherwise specified, all preparation raw materials are commercially available products well known to those skilled in the art.

[0049] In the present invention, the method for preparing the compound having the structure of Formula 2 preferably comprises the following steps:

[0050] 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane, 2,2-bis(4-hydroxyphenyl)hexafluoropropane, perfluorobiphenyl, potassium carbonate and N,N-dimethylacetamide are mixed and subjected to aromatic nucleophilic substitution polycondensation reaction to obtain the compound having the structure of formula 2.

[0051] In the present invention, the molar amount of the perfluorobiphenyl is preferably equal to the sum of the molar amounts of the 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane and the 2,2-bis(4-hydroxyphenyl)hexafluoropropane; the molar ratio of the 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane to the 2,2-bis(4-hydroxyphenyl)hexafluoropropane is preferably (1-4):(9-6), more preferably (2-3):(8-7). The molar ratio of potassium carbonate to perfluorobiphenyl is preferably (1-2):1, more preferably (1.2-1.8):1, and most preferably (1.4-1.6):1; the ratio of the mass of N,N-dimethylacetamide to the total mass of 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane, 2,2-bis(4-hydroxyphenyl)hexafluoropropane and perfluorobiphenyl is preferably (4-6):1, more preferably (4.5-5.5):1. In an embodiment of the present invention, the molar ratio of the 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane to 2,2,-bis(4-hydroxyphenyl)hexafluoropropane is specifically 1:9, 1:4, 3:7 or 4:6; the molar ratio of the potassium carbonate to perfluorobiphenyl is specifically 1.6:1; the ratio of the mass of the N,N-dimethylacetamide to the total mass of the 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane, 2,2,-bis(4-hydroxyphenyl)hexafluoropropane and perfluorobiphenyl is specifically 30:8.0801, 30:10.7697, 30:8.1521 or 30:8.1881.

[0052] In the present invention, the mixing is preferably carried out under nitrogen atmosphere and stirring conditions. The present invention does not have any particular limitation on the mixing process, and the mixing can be carried out using a process well known to those skilled in the art. In an embodiment of the present invention, the mixing is specifically carried out in a three-necked flask equipped with a nitrogen inlet and outlet, a spherical condenser and a mechanical stirrer.

[0053] In the present invention, the temperature of the aromatic nucleophilic substitution polycondensation reaction is preferably 80-90°C, more preferably 82-88°C, and most preferably 84-86°C; the time is preferably 4-6h, more preferably 4.5-5.5h, and most preferably 4.8-5.2h. In an embodiment of the present invention, the temperature of the aromatic nucleophilic substitution polycondensation reaction can be 80°C and the time can be 5h.

[0054] After the aromatic nucleophilic substitution polycondensation reaction is completed, the present invention also preferably includes post-treatment, and the post-treatment includes sedimentation, filtration, washing and drying performed in sequence; the sedimentation is preferably carried out using ethanol; the present invention does not have any special limitations on the specific process of the sedimentation, filtration, washing and drying, and the process familiar to those skilled in the art can be used.

[0055] In the present invention, the molar ratio of the amino group in the compound having the structure shown in Formula 2 to the epoxy group in the compound having the structure shown in Formula 3 is preferably 1:2.

[0056] In the present invention, the organic solvent is preferably one or more of N-methyl-2-pyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide, and tetrahydrofuran, and more preferably N-methyl-2-pyrrolidone. In an embodiment of the present invention, the organic solvent may be N-methyl-2-pyrrolidone. In the present invention, the mass ratio of the compound having the structure shown in Formula 2 to the volume ratio of the organic solvent is preferably 1g: (10-15) mL, and more preferably 1g: (12-13) mL. In an embodiment of the present invention, the mass ratio of the compound having the structure shown in Formula 2 to the volume ratio of the organic solvent may be 1g: 10mL.

[0057] In the present invention, the temperature of the amino-epoxy curing reaction is preferably 100 to 140° C., more preferably 110 to 130° C.; the time is preferably 12 to 24 hours, more preferably 14 to 22 hours.

[0058] In the present invention, the preparation reaction route of the fluorinated polyarylether having a cross-linked network structure is as shown in Formula I:

[0059]

[0060] The present invention also provides the use of the fluorinated polyarylether containing a cross-linked network structure described in the above technical solution or the fluorinated polyarylether containing a cross-linked network structure prepared by the preparation method described in the above technical solution in the field of communications or microelectronics.

[0061] In the present invention, when used, the fluorinated polyarylether having a cross-linked network structure is preferably in the form of a fluorinated polyarylether film.

[0062] In the present invention, the preparation process of the fluorinated polyarylether membrane containing a cross-linked network structure preferably comprises the following steps:

[0063] Mixing a compound having a structure represented by Formula 2, a compound having a structure represented by Formula 3, and an organic solvent to obtain a mixed solution;

[0064] The mixed solution is formed into a film and solidified to obtain a fluorinated polyarylether film.

[0065] In the present invention, the mixing is preferably heating the compound having the structure shown in Formula 2 and fully dissolving it in the organic solvent, cooling it to room temperature, adding the compound having the structure shown in Formula 3, and stirring it evenly. In the present invention, the heating temperature is preferably 50 to 70° C.; the present invention has no special limitation on the stirring process, and the stirring process can be carried out by a process well known to those skilled in the art.

[0066] In the present invention, the film-forming and curing process preferably includes filtering the mixture, coating the mixture on a glass mold, and heating. In the present invention, the filtration is preferably performed using a sand core funnel. In the present invention, the heating is preferably performed in an oven under vacuum conditions; the heating process is preferably sequentially dried at 80°C, 100°C, 120°C, 140°C, 160°C, 180°C, 200°C, 220°C, and 240°C for 2 hours. In the present invention, the heating process preferably includes an amino-epoxy curing reaction process and a film curing process.

[0067] The fluorinated polyarylether membrane with a cross-linked network structure provided by the present invention and its preparation method and application are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0068] Raw materials and sources of raw materials involved in the embodiments:

[0069] 2,2-Bis(4-hydroxyphenyl)hexafluoropropane (bisphenol AF): Tokyo Chemical Industry Co., Ltd., purity>98%;

[0070] 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane: Tokyo Chemical Industry Co., Ltd., purity>98%;

[0071] Perfluorobiphenyl: Wuhan Changcheng Chemical Technology Development Co., Ltd., purity> 98%;

[0072] Anhydrous potassium carbonate (K2CO3): Shanghai Lingfeng Chemical Reagent Co., Ltd., purity ≥99%;

[0073] N,N-dimethylacetamide (DMAc): Shanghai Lingfeng Chemical Reagent Co., Ltd., purity ≥98%;

[0074] 1,6-Hexanediol diglycidyl ether (epoxide value: 0.65-0.70): Shanghai MacLean Biochemical Technology Co., Ltd.;

[0075] N-Methyl-2-pyrrolidone (NMP): Shanghai Lingfeng Chemical Reagent Co., Ltd., purity ≥99%.

[0076] Example 1

[0077] 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane (0.4395 g, 1.2 mmol), 2,2-bis(4-hydroxyphenyl)hexafluoropropane (3.6313 g, 10.8 mmol), perfluorobiphenyl (4.0093 g, 12 mmol), anhydrous potassium carbonate (2.6536 g, 19.2 mmol) and 32 mL of N,N-dimethylacetamide were added to a 100 mL three-necked flask equipped with a nitrogen inlet and outlet, a spherical condenser and a mechanical stirrer. The mixture was reacted at 80 °C for 5 h, and then precipitated in ethanol, filtered, washed and dried in sequence to obtain a fibrous amino-containing fluorinated polyarylether (PAE-1, with a yield of 84%). The molecular weight was measured by a WATERS 515 gel permeation chromatograph, in which tetrahydrofuran was used as a solvent at a flow rate of 1.0 mL / min. The test results showed that the number average molecular weight was 5.64×10 4 g / mol, and the weight average molecular weight is 23.42×10 4 g / mol, the polydispersity index is 4.16, where the value of x is 0.1 and the value of n is 89);

[0078] 2 g of the fibrous amino-structured fluorinated polyarylether was heated (55°C) and fully dissolved in 20 mL of N-methyl-2-pyrrolidone, cooled to room temperature, 0.1860 g of 1,6-hexanediol diglycidyl ether was added, stirred evenly, filtered with a sand core funnel, and then coated on a glass mold, reacted and dried in a vacuum oven (dried at 80°C, 100°C, 120°C, 140°C, 160°C, 180°C, 200°C, 220°C and 240°C for 2 hours in sequence) to obtain an amino and epoxy cross-linked fluorinated polyarylether membrane material (CL-Co-PAE-1).

[0079] Figure 1 For the PAE-1 1 H-NMR (CDCl3, 400 MHz) (recorded by Bruker AVANCEⅢ400M digital nuclear magnetic resonance spectrometer with CDCl3 as solvent) 1 H-NMR spectrum), by Figure 1 It can be seen that the chemical shifts at 6.50-7.75 ppm belong to the protons on the benzene ring, and the chemical shift at 4.06 ppm belongs to the characteristic peak of the amino group.

[0080] Example 2

[0081] 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane (0.8790 g, 2.4 mmol), 2,2-bis(4-hydroxyphenyl)hexafluoropropane (3.2278 g, 9.6 mmol), perfluorobiphenyl (4.0093 g, 12 mmol), anhydrous potassium carbonate (2.6536 g, 19.2 mmol) and 32 mL of N,N-dimethylacetamide were added to a 100 mL three-necked flask equipped with a nitrogen inlet and outlet, a spherical condenser and a mechanical stirrer. The mixture was reacted at 80 °C for 5 h, and then precipitated in ethanol, filtered, washed and dried in sequence to obtain a fibrous amino-containing fluorinated polyarylether (PAE-2, with a yield of 87%). The molecular weight was measured by a WATERS 515 gel permeation chromatograph, in which tetrahydrofuran was used as a solvent at a flow rate of 1.0 mL / min. The test results showed that the number average molecular weight was 5.18×10 4 g / mol, weight average molecular weight is 20.45×10 4 g / mol, the polydispersity index is 3.95, where the value of x is 0.2 and the value of n is 81);

[0082] 2 g of the fibrous amino-structured fluorinated polyarylether was heated (55°C) and fully dissolved in 20 mL of N-methyl-2-pyrrolidone, cooled to room temperature, 0.3702 g of 1,6-hexanediol diglycidyl ether was added, stirred evenly, filtered with a sand core funnel, and then coated on a glass mold, reacted and dried in a vacuum oven (dried at 80°C, 100°C, 120°C, 140°C, 160°C, 180°C, 200°C, 220°C and 240°C for 2 hours in sequence) to obtain an amino and epoxy cross-linked fluorinated polyarylether membrane material (CL-Co-PAE-2).

[0083] Figure 2 For the PAE-2 1 H-NMR (CDCl3, 400 MHz) (recorded by Bruker AVANCEⅢ400M digital nuclear magnetic resonance spectrometer with CDCl3 as solvent) 1 H-NMR spectrum), by Figure 2 It can be seen that the chemical shifts at 6.50-7.75 ppm belong to the protons on the benzene ring, and the chemical shift at 4.06 ppm belongs to the characteristic peak of the amino group.

[0084] Example 3

[0085] 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane (1.3185 g, 3.6 mmol), 2,2-bis(4-hydroxyphenyl)hexafluoropropane (2.8243 g, 8.4 mmol), perfluorobiphenyl (4.0093 g, 12 mmol), anhydrous potassium carbonate (2.6536 g, 19.2 mmol) and 32 mL of N,N-dimethylacetamide were added to a 100 mL three-necked flask equipped with a nitrogen inlet and outlet, a spherical condenser and a mechanical stirrer. The mixture was reacted at 80 °C for 5 h, and then precipitated in ethanol, filtered, washed and dried in sequence to obtain a fibrous amino-containing fluorinated polyarylether (PAE-3, with a yield of 83%). The molecular weight was measured by a WATERS 515 gel permeation chromatograph, in which tetrahydrofuran was used as a solvent at a flow rate of 1.0 mL / min. The test results showed that the number average molecular weight was 4.54×10 4 g / mol, and the weight average molecular weight is 22.61×10 4 g / mol, the polydispersity index is 4.98, where the value of x is 0.3 and the value of n is 71);

[0086] 2 g of the fibrous amino-structured fluorinated polyarylether was heated (55°C) and fully dissolved in 20 mL of N-methyl-2-pyrrolidone, cooled to room temperature, 0.5528 g of 1,6-hexanediol diglycidyl ether was added, stirred evenly, filtered with a sand core funnel, and then coated on a glass mold, reacted and dried in a vacuum oven (dried at 80°C, 100°C, 120°C, 140°C, 160°C, 180°C, 200°C, 220°C and 240°C for 2 hours in sequence) to obtain an amino and epoxy cross-linked fluorinated polyarylether membrane material (CL-Co-PAE-3).

[0087] Figure 3 For the PAE-3 1 H-NMR (CDCl3, 400 MHz) (recorded by Bruker AVANCEⅢ400M digital nuclear magnetic resonance spectrometer with CDCl3 as solvent) 1 H-NMR spectrum), by Figure 3 It can be seen that the chemical shifts at 6.50-7.75 ppm belong to the protons on the benzene ring, and the chemical shift at 4.06 ppm belongs to the characteristic peak of the amino group.

[0088] Example 4

[0089] 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane (1.7580 g, 4.8 mmol), 2,2-bis(4-hydroxyphenyl)hexafluoropropane (2.4208 g, 7.2 mmol), perfluorobiphenyl (4.0093 g, 12 mmol), anhydrous potassium carbonate (2.6536 g, 19.2 mmol) and 32 mL of N,N-dimethylacetamide were added to a 100 mL three-necked flask equipped with a nitrogen inlet and outlet, a spherical condenser and a mechanical stirrer. The mixture was reacted at 80 °C for 5 h, and then precipitated in ethanol, filtered, washed and dried in sequence to obtain a fibrous amino-containing fluorinated polyarylether (PAE-4, with a yield of 89%). The molecular weight was measured by a WATERS 515 gel permeation chromatograph, in which tetrahydrofuran was used as a solvent at a flow rate of 1.0 mL / min. The test results showed that the number average molecular weight was 4.28×10 4 g / mol, weight average molecular weight is 20.30×10 4 g / mol, the polydispersity index is 4.74, where the value of x is 0.4 and the value of n is 67);

[0090] 2 g of the fibrous amino-structured fluorinated polyarylether was heated (55°C) and fully dissolved in 20 mL of N-methyl-2-pyrrolidone, cooled to room temperature, 0.7336 g of 1,6-hexanediol diglycidyl ether was added, stirred evenly, filtered with a sand core funnel, and then coated on a glass mold, reacted and dried in a vacuum oven (dried at 80°C, 100°C, 120°C, 140°C, 160°C, 180°C, 200°C, 220°C and 240°C for 2 hours in sequence) to obtain an amino and epoxy cross-linked fluorinated polyarylether membrane material (CL-Co-PAE-4).

[0091] Figure 4 For the PAE-4 1 H-NMR (CDCl3, 400 MHz) (recorded by Bruker AVANCEⅢ400M digital nuclear magnetic resonance spectrometer with CDCl3 as solvent) 1 H-NMR spectrum), by Figure 4 It can be seen that the chemical shift of 6.50-7.75ppm belongs to the protons on the benzene ring. The chemical shift at 4.06ppm is attributed to the characteristic peak of the amino group;

[0092] Figure 5 The fibrous amino-containing fluorinated polyarylether (PAE-1, PAE-2, PAE-3 and PAE-4) described in Examples 1 to 4 are partially 1 H-NMR diagram (test method: recorded by Bruker AVANCEⅢ400M digital nuclear magnetic resonance spectrometer with CDCl3 as solvent) 1H-NMR spectrum), by Figure 5 It can be seen that as the content of 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane increases, the signal of the amino group increases.

[0093] Comparative Example 1

[0094] PAE-1 was prepared by referring to the preparation method described in Example 1;

[0095] 2 g of the PAE-1 was heated and fully dissolved in 20 mL of N-methyl-2-pyrrolidone, filtered with a sand core funnel and coated on a glass mold, and dried in an oven at 80°C, 100°C, 120°C, 140°C, 160°C, 180°C and 200°C for 2 h to obtain an amino structure-containing fluorinated polyarylether film (Co-PAE-1).

[0096] Comparative Example 2

[0097] PAE-2 was prepared by referring to the preparation method described in Example 2;

[0098] 2 g of the PAE-2 was heated and fully dissolved in 20 mL of N-methyl-2-pyrrolidone, filtered with a sand core funnel and coated on a glass mold, and dried in an oven at 80°C, 100°C, 120°C, 140°C, 160°C, 180°C and 200°C for 2 h to obtain an amino structure-containing fluorinated polyarylether film (Co-PAE-2).

[0099] Comparative Example 3

[0100] PAE-3 was prepared by referring to the preparation method described in Example 3;

[0101] 2 g of the PAE-3 was heated and fully dissolved in 20 mL of N-methyl-2-pyrrolidone, filtered with a sand core funnel and coated on a glass mold, and dried in an oven at 80°C, 100°C, 120°C, 140°C, 160°C, 180°C and 200°C for 2 h to obtain an amino structure-containing fluorinated polyarylether film (Co-PAE-3).

[0102] Comparative Example 4

[0103] PAE-4 was prepared by referring to the preparation method described in Example 4;

[0104] 2 g of the PAE-4 was heated and fully dissolved in 20 mL of N-methyl-2-pyrrolidone, filtered with a sand core funnel and coated on a glass mold, and dried in an oven at 80°C, 100°C, 120°C, 140°C, 160°C, 180°C and 200°C for 2 h to obtain an amino structure-containing fluorinated polyarylether film (Co-PAE-4).

[0105] Figure 6 The infrared comparison spectra of Co-PAE-4 described in Comparative Example 4 and CL-Co-PAE-4 described in Example 4 (Test method: FTIR spectra (4000-400 cm) were recorded on a Nicolet IS 50 Fourier transform infrared spectrometer produced by Thermo Fisher Scientific -1 )),Depend on Figure 6 It can be seen that 1608cm -1 、1650cm -1 、1501cm -1 The absorption peak of 1181cm is attributed to the skeleton vibration of the benzene ring. -1 The characteristic peak at 1229cm is attributed to trifluoroisopropyl. -1 、1072cm -1 The characteristic peaks at 982cm are attributed to the asymmetric and symmetric vibration peaks of the aromatic ether bond. -1 The peak at 726cm is attributed to the CF bond. -1 The out-of-plane bending of aromatic -CH bonds is attributed to the 3407 cm -1 、3497cm -1 The absorption peak at 1627 cm is attributed to the stretching vibration of NH. -1 The bending vibration peak at 3451cm is attributed to NH. In the infrared spectrum of CL-Co-PAE-4, the characteristic peak of NH disappears, and the peak at 3451cm -1 The characteristic peak of -OH appeared at 2853cm -1 、2932cm -1 The peak of the methylene group becomes stronger;

[0106] Figure 7 The relationship between the dielectric constant and the electric field frequency of Co-PAE-1 described in Comparative Example 1, Co-PAE-2 described in Comparative Example 2, Co-PAE-3 described in Comparative Example 3, Co-PAE-4 described in Comparative Example 4, CL-Co-PAE-1 described in Example 1, CL-Co-PAE-2 described in Example 2, CL-Co-PAE-3 described in Example 3, and CL-Co-PAE-4 described in Example 4 (test method: conducted by TH2826 type LCR digital bridge. The test was conducted at room temperature, and the frequency range was 10~10 6 Hz), by Figure 7It can be seen that the dielectric constant decreases with increasing frequency. For Co-PAE-1 described in Comparative Example 1, Co-PAE-2 described in Comparative Example 2, Co-PAE-3 described in Comparative Example 3, and Co-PAE-4 described in Comparative Example 4, as the content of 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane increases, the cross-linked network increases and the dielectric constant decreases. And the dielectric constants of CL-Co-PAE-1 described in Example 1, CL-Co-PAE-2 described in Example 2, CL-Co-PAE-3 described in Example 3, and CL-Co-PAE-4 described in Example 4 are all lower than those of Co-PAE-1 described in Comparative Example 1, Co-PAE-2 described in Comparative Example 2, Co-PAE-3 described in Comparative Example 3, and Co-PAE-4 described in Comparative Example 4, which is due to the formation of a cross-linked network;

[0107] Table 1 shows the thermal properties of Co-PAE-1 described in Comparative Example 1, Co-PAE-2 described in Comparative Example 2, Co-PAE-3 described in Comparative Example 3, Co-PAE-4 described in Comparative Example 4, CL-Co-PAE-1 described in Example 1, CL-Co-PAE-2 described in Example 2, CL-Co-PAE-3 described in Example 3 and CL-Co-PAE-4 described in Example 4, wherein the testing method is as follows: Thermogravimetric analysis is obtained by testing with a TG209F3 thermogravimetric analyzer, and the testing conditions are under a nitrogen environment, with the heating rate rising from 50°C to 800°C at a rate of 20°C / min. The glass transition temperature was obtained by testing with a Pyris 1 differential scanning calorimeter produced by Perkin Elmer, and the test conditions were a heating rate of 10°C / min from 50°C to 300°C in a nitrogen environment; as shown in Table 1, for Co-PAE-1 described in Comparative Example 1, Co-PAE-2 described in Comparative Example 2, Co-PAE-3 described in Comparative Example 3, and Co-PAE-4 described in Comparative Example 4, as the content of 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane increases, the content of polar amino groups increases, the intermolecular forces increase, and the glass transition temperature increases. For CL-Co-PAE-1 described in Example 1, CL-Co-PAE-2 described in Example 2, CL-Co-PAE-3 described in Example 3, and CL-Co-PAE-4 described in Example 4, as the content of 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane increases, the cross-linking network increases, the degree of hindrance to chain segment motion increases, and the glass transition temperature increases. It can also be seen that compared with the film before cross-linking, the glass transition temperature of the film after cross-linking is increased. The temperatures at which the weight loss of Co-PAE-1 described in Comparative Example 1, Co-PAE-2 described in Comparative Example 2, Co-PAE-3 described in Comparative Example 3, Co-PAE-4 described in Comparative Example 4, CL-Co-PAE-1 described in Example 1, CL-Co-PAE-2 described in Example 2, CL-Co-PAE-3 described in Example 3, and CL-Co-PAE-4 described in Example 4 was 5% decreased with the increase of the content of 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane. Before cross-linking, the thermal stability of the amino group is inferior to that of the main chain containing rigid benzene rings; after cross-linking, the CC bond energy of the cross-linked network is lower than that of the main chain containing rigid benzene rings. And the sample T after cross-linking 5% Both are improved and thermal stability is increased.

[0108] Table 1 Thermal properties of Co-PAE-1 described in Comparative Example 1, Co-PAE-2 described in Comparative Example 2, Co-PAE-3 described in Comparative Example 3, Co-PAE-4 described in Comparative Example 4, CL-Co-PAE-1 described in Example 1, CL-Co-PAE-2 described in Example 2, CL-Co-PAE-3 described in Example 3, and CL-Co-PAE-4 described in Example 4

[0109] sample <![CDATA[T 5% (℃)]]> <![CDATA[T max (℃)]]> <![CDATA[T g (℃)]]> Co-PAE-1 505 557 157 Co-PAE-2 438 578 179 Co-PAE-3 420 567 181 Co-PAE-4 413 572 184 CL-Co-PAE-1 526 573 183 CL-Co-PAE-2 524 543 187 CL-Co-PAE-3 506 547 193 CL-Co-PAE-4 419 571 195

[0110] Note: 5% is the temperature at which the weight loss is 5%; T max is the temperature at which the decomposition rate is maximum; T g is the glass transition temperature

[0111] Table 2 shows the mechanical properties of Co-PAE-1 described in Comparative Example 1, Co-PAE-2 described in Comparative Example 2, Co-PAE-3 described in Comparative Example 3, Co-PAE-4 described in Comparative Example 4, CL-Co-PAE-1 described in Example 1, CL-Co-PAE-2 described in Example 2, CL-Co-PAE-3 described in Example 3 and CL-Co-PAE-4 described in Example 4; wherein the test method is: tested by WDT-10 electronic universal testing machine, the film size is 5cm×1cm, the test stretching rate is 5mm / min , the experiment was repeated 5 times to take the average value; as shown in Table 2, the tensile strength and tensile modulus of CL-Co-PAE-1 described in Example 1, CL-Co-PAE-2 described in Example 2, CL-Co-PAE-3 described in Example 3, and CL-Co-PAE-4 described in Example 4 are higher than those of Co-PAE-1 described in Comparative Example 1, Co-PAE-2 described in Comparative Example 2, Co-PAE-3 described in Comparative Example 3, and Co-PAE-4 described in Comparative Example 4, because the cross-linked network hinders the movement of the polymer chain, the polymer rigidity increases, and the tensile strength increases. And with the increase of the cross-linked network, the tensile strength and tensile modulus of CL-Co-PAE-1 described in Example 1, CL-Co-PAE-2 described in Example 2, CL-Co-PAE-3 described in Example 3, and CL-Co-PAE-4 described in Example 4 first increase and then decrease. The increase is due to the increase of the cross-linked network, and the decrease is due to the transition cross-linking.

[0112] Table 2 Mechanical properties of Co-PAE-1 described in Comparative Example 1, Co-PAE-2 described in Comparative Example 2, Co-PAE-3 described in Comparative Example 3, Co-PAE-4 described in Comparative Example 4, CL-Co-PAE-1 described in Example 1, CL-Co-PAE-2 described in Example 2, CL-Co-PAE-3 described in Example 3, and CL-Co-PAE-4 described in Example 4

[0113] sample Tensile strength(MPa) Tensile modulus(GPa) Elongation at break (%) Co-PAE-1 36.0 1.2 4.5 Co-PAE-2 48.9 1.3 5.5 Co-PAE-3 52.1 1.3 7.5 Co-PAE-4 53.2 1.6 4.7 CL-Co-PAE-1 43.2 2.0 3.5 CL-Co-PAE-2 61.8 2.1 5.3 CL-Co-PAE-3 77.1 2.1 7.1 CL-Co-PAE-4 65.5 2.0 4.3

[0114] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A fluorinated polyarylether having a cross-linked network structure, characterized in that: It has the structure shown in formula 1: Among them, the value range of x is 0.1~0.4, and the value range of n is 60~90.

2. The method for preparing the fluorinated polyarylether having a cross-linked network structure according to claim 1, characterized in that: The following steps are involved: Carrying out an amino-epoxy curing reaction of a compound having a structure represented by Formula 2 and a compound having a structure represented by Formula 3 in an organic solvent to obtain the fluorinated polyarylether having a cross-linked network structure; Among them, the value range of x is 0.1~0.4, and the value range of n is 60~90.

3. The preparation method according to claim 2, characterized in that: The molar ratio of the amino group in the compound having the structure shown in Formula 2 to the epoxy group in the compound having the structure shown in Formula 3 is 1:

2.

4. The preparation method according to claim 2 or 3, characterized in that: The method for preparing the compound having the structure of formula 2 comprises the following steps: 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane, 2,2-bis(4-hydroxyphenyl)hexafluoropropane, perfluorobiphenyl, potassium carbonate and N,N-dimethylacetamide are mixed and subjected to aromatic nucleophilic polycondensation reaction to obtain the compound having the structure of formula 2.

5. The preparation method according to claim 4, characterized in that: The molar amount of the perfluorobiphenyl is equal to the sum of the molar amounts of the 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane and the 2,2-bis(4-hydroxyphenyl)hexafluoropropane; The molar ratio of the 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane to the 2,2-bis(4-hydroxyphenyl)hexafluoropropane is (1-4):(9-6).

6. The preparation method according to claim 4 or 5, characterized in that: The molar ratio of potassium carbonate to perfluorobiphenyl is (1-2):1; The ratio of the mass of the N,N-dimethylacetamide to the total mass of the 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane, 2,2-bis(4-hydroxyphenyl)hexafluoropropane and perfluorobiphenyl is (4-6):

1.

7. The preparation method according to claim 4, characterized in that: The temperature of the aromatic nucleophilic polycondensation reaction is 80-90° C. and the time is 4-6 hours.

8. The preparation method according to claim 2, characterized in that: The temperature of the amino-epoxy curing reaction is 100-140° C. and the time is 12-24 hours.

9. Use of the fluorinated polyarylether containing a cross-linked network structure according to claim 1 or the fluorinated polyarylether containing a cross-linked network structure prepared by the preparation method according to any one of claims 2 to 8 in the field of communications or microelectronics.

10. The use according to claim 9, characterized in that: The fluorinated polyarylether containing a cross-linked network structure is in the form of a fluorinated polyarylether membrane, and the preparation process of the fluorinated polyarylether membrane comprises the following steps: Mixing a compound having a structure represented by Formula 2, a compound having a structure represented by Formula 3, and an organic solvent to obtain a mixed solution; The mixed solution is formed into a film and solidified to obtain a fluorinated polyarylether film.

Citation Information

Patent Citations

  • Dimension-stable low-dielectric polyimide film and preparation method and application thereof

    CN114316591A

  • Fluorine-containing polyarylether, electrolyte solution of fluorine-containing polyarylether, and preparation method and application of proton exchange membrane

    CN115746290A

  • Epoxy resin composite material and preparation method and composition thereof

    CN118638461A

  • Member for display and method of manufacturing the same

    JP2011077251A

Cited By

  • Crosslinked polyarylether membrane material containing bismaleimide structure as well as preparation method and application of crosslinked polyarylether membrane material

    CN120059161A